2021
DOI: 10.1017/langcog.2020.34
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of animation versus static effects in the spatial concept-based metaphor awareness-raising approach on EFL learners’ cognitive processing of request strategies

Abstract: This study evaluates the relative effects of two cognitive linguistic approaches – using animated versus static scenes in an illustration based on the spatial concept-oriented metaphor – and a non-cognitive linguistic approach on the Japanese EFL learners’ processing of request strategies with degrees of politeness. The cognitive linguistic approach consisted of applying the metaphor politeness is distance in the teaching of different degrees of politeness. It involved a spatial concept projection through whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 39 publications
0
9
0
Order By: Relevance
“…The results of the acceptability judgement tests indicated that the static version enabled participants to perform as well as those who used the animated version, and both groups performed significantly better than the non‐metaphor awareness‐raising group, which was instructed to recollect a list of different target expressions. The metaphor awareness‐raising approaches with 2D images—animated or static—had a strong impact on the overall performance of both groups in Takimoto (2021) study. However, 2D images consist of only height and width, which might have caused the animation to play no role in making the spatial relationships of near–far and high–low more realistic in the metaphor awareness‐raising approach.…”
Section: Literature Reviewmentioning
confidence: 96%
See 3 more Smart Citations
“…The results of the acceptability judgement tests indicated that the static version enabled participants to perform as well as those who used the animated version, and both groups performed significantly better than the non‐metaphor awareness‐raising group, which was instructed to recollect a list of different target expressions. The metaphor awareness‐raising approaches with 2D images—animated or static—had a strong impact on the overall performance of both groups in Takimoto (2021) study. However, 2D images consist of only height and width, which might have caused the animation to play no role in making the spatial relationships of near–far and high–low more realistic in the metaphor awareness‐raising approach.…”
Section: Literature Reviewmentioning
confidence: 96%
“…Recent metaphor awareness-raising approach studies have evaluated the efficacy of animated visualisation in teaching German grammar, such as motion verbs (Roche & Scheller, 2008), passive voice (Arnett et al, 2019), case systems (Gradel, 2016), modal verbs (Kanaplianik, 2016), and light verbs (Suñer & Roche, 2019); and in teaching English, such as vocabulary (Sato et al, 2021) and degrees of politeness (Takimoto, 2021). All studies compared the metaphor awareness-raising and non-metaphorical instructional approaches without a control group (Arnett et al, 2019;Gradel, 2016;Kanaplianik, 2016;Roche & Scheller, 2008;Sato et al, 2021;Suñer & Roche, 2019) The studies by Gradel (2016) and Suñer and Roche (2019) compared the animated metaphor awareness-raising approach and teacher-directed traditional teaching approach.…”
Section: Animated Visualisation In the Metaphor Awareness-raising App...mentioning
confidence: 99%
See 2 more Smart Citations
“…5G technology can effectively improve the spectral efficiency and link reliability of the system by employing multiple antenna arrays at the transceiver end and using the variability of channel fading at different antenna array locations to obtain spatial diversity or multiplexing gain, which has been widely used in communication systems in recent years [18]. The key technology in 5G and B5G systems, compared to the traditional 2D5G technology, extends the arrangement of antenna arrays to 3D space and flexibly controls the weights of each array element in 3D space to achieve 3D beam assignment, thus further enhancing the spectral efficiency of the system.…”
Section: Research On Teaching Mode Of Animationmentioning
confidence: 99%